CHARACTER BUILDING AND THE INCREASE OF STUDENT ACTIVITY IN LESSON STUDY PRACTICE - Sri Walji Hasthanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
This article is based on the result of observing students grade 4 of SD Muhammadiyah (Plus) Salatiga. The observation is carried out as part of character development and increase student activity using Lesson Study model during Mathematics lessons. The subject of the study are 16 students of grade 4 consisting of 9 males and 7 females. The data obtained through observation, interviews, literature study and field notes. The approach of the study is qualitative by using descriptive analysis method to describe and interpret objects as they are. The study shows a promising result in students‟ character development through repeated enforcement using the Lesson Study. This is shown by the prominent characteristics such as honesty, independence, tolerance, respecting others‟ opinions, self-confidence, and creativity. Students‟ activities encompassing Visual Activities, Oral Activities and Emotional Activities have also shown to be in the increase. The students were very enthusiastic which is shown from the percentage of those in the very good category 37.5% (5 students) and good category 43.75% (8 students).Key words: character development, students’ active participation, Lesson Study.